A large eddy simulation of flows around an underwater vehicle model using an immersed boundary method. Issue 6 (November 2016) - Wang, Shizhao; Shi, Beiji; Li, Yuhang; He, Guowei
Abstract: A large eddy simulation (LES) of the flows around an underwater vehicle model at intermediate Reynolds numbers is performed. The underwater vehicle model is taken as the DARPA SUBOFF with full appendages, where the Reynolds number based on the hull length is 1.0 × 10 5 . An immersed boundary method based on the moving-least-squares reconstruction is used to handle the complex geometric boundaries. The adaptive mesh refinement is utilized to resolve the flows near the hull. The parallel scalabilities of the flow solver are tested on meshes with the number of cells varying from 50 million to 3.2 billion. The parallel solver reaches nearly linear scalability for the flows around the underwater vehicle model. The present simulation captures the essential features of the vortex structures near the hull and in the wake. Both of the time-averaged pressure coefficients and streamwise velocity profiles obtained from the LES are consistent with the characteristics of the flows pass an appended axisymmetric body. The code efficiency and its correct predictions on flow features allow us to perform the full-scale simulations on tens of thousands of cores with billions of grid points for higher-Reynolds-number flows around the underwater vehicles. Highlights: The velocity self-similarity of wake is predicted by using large-eddy simulation. Diffuse interface immersed boundary method is coupled with large eddy simulation. The flow solver with IB method shows nearly linear parallel scalabilities.